Tri-ponderal mass index and body mass index for estimating body fat in children in Surakarta, Indonesia - Moelyo, Annang Giri; Nisa, Azzahra Fadhlila Aulia; Astuti, Anita Sefti; Mardiyah, Putri Ma’rifatul; Azzainabi, Nur Fatimah Nikmatullah; Kumala, Soebhita Hema; Rahayu, Cynthia Octaviani; Purnata, Lyviana Patrishia; Marcellia, Stefany; Prisola, Steiner Lukas (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2022)
Background: The body mass index parameter is currently used to determine obesity (excess body fat) in children. Using this measure has limitations in predicting body fat, particularly in adolescents. An alternative parameter to predict body fat is the tri-ponderal mass index (TMI).Objective: The study aims to investigate the different patterns between body mass index and triponderal mass index in children and to determine the correlation of body mass index (BMI) or TMI as a predictor of body fat.Methods: This cross-sectional study of 351 subjects aged 6-18 in Surakarta (241 females; 110 males). All subjects underwent anthropometric measurements (height and weight) and body fat percentage measurements. We used equations for predicting the percent body fat in boys and girls based on their TMI and BMI.Results: TMI and BMI overall means were 13.3±2.9 vs 20.2±4.7. Among subjects less and more than 12 years, the TMI and BMI means were 13.3±2.1 vs 17.9±3.6. and 13.3±3.1 vs 20.7±4.8. The adjusted R2 of equations for predicting percent body fat based TMI and BMI were 0.76 vs 0.33 in boys and 0.89 vs 0.87 in girls).Conclusions: TMI showed greater stability with age than BMI. TMI was a better predictor for body fat percentage than BMI for both sexes, especially in boys. It is worth considering replacing body mass index with triponderal mass index to estimate body fat percentage in boys.